21 A Phase II Study of Total Consolidative Metastasis-and-Primary Directed Therapy for Renal Cell Carcinoma (NCT06770855) - Henry Litt; Jeffrey Shevach; Ryan Cobb; Arun Goel; Thomas Guzzo; Daniel Lee; Lin Mei; Ronac Mamtani; Kara Maxwell; Vivek Narayan; John Nikitas; Phillip Pierorazio; et al. (The Oncologist, 2026)
Abstract Background Immunotherapy (IO)-based frontline therapy has improved outcomes for patients with metastatic renal cell carcinoma (RCC), with some patients achieving a complete response (CR). Patients who achieve CR are most likely to have sustained responses, whereas patients achieving stable disease (SD) or partial response (PR) often progress despite ongoing therapy. Most progression events occur at pre-existing disease sites, emphasizing the need to augment first-line therapy in this population. Methods This is a single-arm, single-institution phase II study. Key eligibility criteria are (1) metastatic clear cell RCC that has been treated with IO-based frontline therapy for 6-12 months, (2) 5 or less metastatic sites, excluding pulmonary nodules <1.0cm, (3) SD or PR after initiating IO-based therapy and (4) disease amenable to metastasis-and-primary directed therapy (MPDT) with surgery, radiation, and/or ablation. Upon enrollment, patients will stop IO-based therapy and undergo MPDT, after which they will be observed without resuming systemic therapy. The primary endpoint is treatment-free survival (TFS), defined as the time from discontinuing systemic therapy until resumption of systemic therapy or death. TFS was chosen because it captures a goal central to many patients: maintaining disease control without ongoing systemic therapy. The secondary endpoints are (1) recurrence-free survival and (2) Grade 3 or higher adverse events according to the CTCAE v5.0. The 12-month TFS rate will be estimated using the Kaplan-Meier method in the per-protocol population, reported with 90% confidence intervals, and compared against the reference value of 13%, which is the estimated 1-year TFS for patients who stop IO-based therapy after achieving CR or PR (Tzeng J et al., Immunother Cancer, 2021). Patients will be enrolled into two pre-specified cohorts based on their systemic regimen: Cohort A (IO/IO) and Cohort B (IO/VEGF-TKI), with a minimum of 8 patients per cohort. Descriptive sub-group analyses of TFS will be performed between cohorts. The target sample size is 24 subjects, which was calculated based on an estimated 12-month TFS rate of 34% among patients undergoing MPDT. This sample provides 80% power for a one-sample log-rank test using one-sided α = 0.05 and includes a 10% dropout/lost to follow-up adjustment. Peripheral blood and tissue samples will be analyzed to identify immune signatures that correlate with TFS of at least 1 year. Peripheral blood samples will be collected at baseline, 3 and 6 weeks after initiating systemic therapy, prior to MPDT, and at time of recurrence or 12 months after stopping systemic therapy. Tumor specimens will also be analyzed to evaluate correlation between nuclear speckle states and TFS. Results This trial addresses an important need in metastatic RCC: the lack of prospective evidence for consolidative local therapies among patients with residual disease after initiating treatment with IO-based therapy. While IO-based treatments have transformed outcomes, most patients achieve SD or PR and remain on systemic therapy until progression, leading to drug-related, financial, and time toxicities. By testing whether MPDT can enable long treatment-free intervals, this study targets a common clinical scenario and uses an endpoint that is meaningful to many patients. This trial also contributes to the understanding of the role of surgery in metastatic RCC. Evidence for upfront cytoreductive nephrectomy has been mixed, with the CARMENA trial demonstrating that immediate surgery may not benefit and possibly harm patients with intermediate- or poor-risk disease. Our approach inverts this paradigm by reserving surgery and other local therapies for patients who demonstrate disease control on systemic therapy, selecting for a biology more likely to benefit from consolidative intervention. If MPDT yields durable TFS, this trial will establish the foundation for a randomized, multi-center study comparing MPDT versus continued systemic therapy, potentially reshaping management of oligometastatic RCC. Conclusions N/A.